Chińczycy. Giganci biznesu czy bezbronni niewolnicy? Postawy rezydentów bliskich i odmiennych kulturowo państw wobec Chińczyków = Are the Chinese business giants or helpless slaves? Attitudes towards Chinese people among residents of culturally close and different countries - Taczkowska, Kalina Maria (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The People`s Republic of China is the fourth largest source of emigrants and the world`s largest source of international students. This is hardly surprising, given China`s population and the increasing travel of Chinese citizens. The focus of this paper is to explore the perceptions and attitudes of individuals in countries that receive Chinese migrants, tourists and students. It is imperative to objectively analyse how they shape their attitudes towards the Chinese.
Keywords: the Chinese; attitude; cultural diversity; migration; own and foreign; Chińczycy; postawa; zróżnicowanie kulturowe; migracja; swój i obcy